Kesan pembelajaran secara simulasi bagi topik keseimbangan daya berdasarkan gabungan teori pembelajaran behaviorisme dan konstruktivisme - Mohd Nizar, Mohd Najib (2024)
Mastery of Physics is closely linked to fields such as engineering, astronomy, education, Mathematics, electronics, and other scientific disciplines. Understanding key concepts and being able to apply Physics knowledge in real-life situations contribute significantly to a country's development. However, misconceptions in physics often arise from inadequate understanding or lack of mastery of fundamental concepts. In Malaysia, high school students' proficiency in Physics is not particularly strong. This is partly due to the reliance on traditional teaching methods. This study aims to examine the effectiveness of using web-based interactive simulations Physics Education Technology for teaching the topic of Forces in Equilibrium. The learning process is supported by a Physics Interactive Simulation Learning Module developed by the researcher. A mixed-methods research design, incorporating quantitative and qualitative approaches was used. The sample included 61 Form Four Science Stream students from two regular day secondary schools in the Kuala Muda/Yan District of Kedah. 31 students were assigned to the experimental group, while 30 students formed the control group. Four students from the experimental group were selected for interviews. The results of the study show that there is a significant difference in the mean pre-test (9.27) and post-test (13.20) scores for the experimental group compared to the control group with the pre-test and post-test mean being 9.47 and 9.33 respectively. Using Physics Education Technology simulations in Physics, combined with behaviorism and constructivism theories, has fostered active learning, self-study, social interaction, conceptual understanding, interest, and high motivation, leading to improved achievement in the Forces in Equilibrium topic. Although suitable for use in class and PdPR, the limitation is time constraints and excessive workload for students. This study contributes to knowledge about teaching Physics through web-based interactive simulations in Malaysian secondary schools. Additionally, the simulation-based learning method and module can support Physics teachers in teaching the Forces in Equilibrium concept.